Cli-fi and class : socioeconomic justice in contemporary American climate fiction - Rosenthal, Debra J., 1964-; Molesky, Jason de Lara, 1985- (Under the sign of nature., 2023)
"The essays in this collection analyze the complex interplays between climate change and inequalities of wealth and power in best-selling popular novels, science fiction titles, literary novels, Hollywood films, and Broadway plays, among other forms"--